PENDIDIKAN FORMAL DALAM NOVEL-NOVEL BALAI PUSTAKA: ANALISIS WACANA KRITIS - Saeful Anwar (CARAKA, 2020)
In the beginning of its emergence, modern Indonesian literary works have taken formal education as the theme. The existence of formal education in the novel is believed as an attempt to build a discourse structure of the Nederlandsch-Indies through Balai Pustaka . In defining the discourse built by Balai Pustaka the research used the theory of critical discourse analysis. This finding then comes to conclusions; firstly, the authors experienced the demeanor ambivalence facing Balai Pustaka which will publish their works. Secondly, formal education was intentionally taken as a theme to show the authors’ resistance toward the Dutch Indies especially to Balai Pustaka, that the formal education was not fully compatible to the native in that era. Therefore it should be suited to the norms and custom at that time.